The Dual-Channel, Pulse-Counting Pierce-Blitzstein Photometer–The PBPHOT: Our Last Paper with Bob Koch, and Additional Technical History - Carol Ambruster; Tony Hull; Robert H. Koch; Rich Mitchell; George Wolf; Bob Smith (Journal of Astronomy and Space Sciences, 2012)
The dual channel Pierce-Blitzstein photometer (PBPHOT) was productively used at the Flower and Cook Observatory to provide 60 years of study of binary systems and other cosmic objects. We review the history of this instrument, discuss its calibration, and recall some personal and professional interactions with Professor Robert H. Koch.